A systematic review and meta-analysis of individual and couple therapies for posttraumatic stress disorder: Clinical and intimate relationship outcomes. (October 2022) - Sijercic, Iris; Liebman, Rachel E.; Ip, Jennifer; Whitfield, Kristen M.; Ennis, Naomi; Sumantry, David; Sippel, Lauren M.; Fredman, Steffany J.; Monson, Candice M.
Abstract: The association between symptoms of posttraumatic stress disorder (PTSD) in adults and difficulties in intimate relationships is well documented. Growing literature suggests that interpersonally-oriented therapies, such as couple and family interventions, may lead to improvements in both PTSD symptoms and intimate relationship functioning. However, it is unknown how individual PTSD treatments compare to couple/family interventions in relational outcomes. The present study was a systematic review and meta-analysis of individual and couple/family treatments to examine changes in PTSD symptoms and intimate relationship functioning. Twelve couple treatment studies with 13 unique samples and 7 individual treatment studies with 9 unique samples met inclusion criteria. No family-based treatments were identified. Meta-analytic findings indicated moderate to large reductions in PTSD symptoms for both couple and individual studies. Small but significant improvements in intimate relationship functioning across individual and couple studies were observed. Moderation analysis suggested that across both individual and couple treatment formats, trauma-focused treatments had larger effects on PTSD symptoms. Trauma-focused treatments had larger effects on intimate relationship functioning for individual studies. Military status did not moderate outcomes. This study supports the utility of both individual and couple treatment formats for treating PTSD and provides preliminary support for these modalities for also enhancing intimate relationship functioning. Highlights: Conducted systematic review and meta-analysis of PTSD therapies. Examined changes in PTSD and intimate relationship functioning outcomes. 12 couple studies and 7 individual studies met inclusion criteria. Moderate-large effects in PTSD and small effects in relationship functioning found. Trauma-focused treatments had larger effects on PTSD outcomes.